Pemanfaatan Tanaman Jagung Sebagai Seni Menghias Kuku - Nurulisma Saputri; Ch Maharani Intan Permatasari; Sofia Daniati (Garina, 2024)
Corn plants are one of the most important carbohydrates producing plants in the world, apart from wheat and rice. Generally corn plants are just useded with the seeds. The lot of corn plant as art of decorating nails as a new innovation in the fields of nailart. The purpose of the research is to know how to use of corn plants as the art of decorating nails them in spring, knowing the result of validation of nailart product by utilizing corn skin, knowing the results of the public favorite level of nailart by utilizing corn skin. The research was carried out by observation methods, experiments, documentation, library, and questionnaire (inquiry). The manufacture of nailart from the corn plant is carried out three stages, namely corn skin drying, preparation of tools and ingredients for decorating nails from corn plants, and the stages of making art adorn the nails from corn plants. The validation outcomes of product validation of 6 validator choose product 3 because it fits the theme spring. The result of the favorite test to 20 respondents through google form total overall can be concluded 96,5% of respondent like and agree with the presence of nailart product from corn plants. Research suggestions need a special measurement on flower petals so that a consistent shape. When processed the corn skin is vulnerable to tears, drying should not be too long